The economics of consumer credit - Bertola, Giuseppe; Disney, Richard; Grant, Charles (Charles Benedict) (MIT Press, 2006)
Academic research and policy discussions of credit markets usually focus on borrowing by firms and producers rather than by households, which are typically analyzed in terms of their savings and portfolio choices. The Economics of Consumer Credit brings together leading international researchers to focus specifically on consumer debt, presenting current empirical and theoretical research crucial to ongoing policy debates on such topics as privacy rules, the regulation of contractual responsibilities, financial stability, and overindebtedness. The rapidly developing consumer credit industry in the United States is mirrored by that in Europe, and this volume is noteworthy for its cross-national perspective. Several chapters compare the use of credit markets by households in different countries, while others focus on single country case studies--including consumer credit dynamics in Italy, the role of housing expenditure in the cyclical pattern of borrowing in the United Kingdom, and the use of credit cards by U.S. consumers--to illustrate general insights. Other chapters draw policy lessons from the U.S. experience with bankruptcy regulation and the development of the credit counseling industry. Finally, the book reviews historical, theoretical, and empirical aspects of information sharing, of particular interest in light of the integration of European Union credit markets. ContributorsCarol C. Bertaut, Giuseppe Bertola, Sarah Bridges, Luca Casolaro, Jonathan Crook, Richard Disney, Leonardo Gambacorta, Charles Grant, Luigi Guiso, Michael Haliassos, Andrew Henley, Robert M. Hunt, Tullio Jappelli, Nicola Jentzsch, Marco Pagano, Amparo San Jose Riestra, Michael Staten, Michelle J. White